Mindfulness-Based Stress Reduction Techniques Among Healthcare Workers in South India: A Regional Analysis of Efficacy and Barriers - Eric Kwasi Elliason; Atul Khajuria; Christian Geudere; Stephen Monday; J. Samuel Kamanda (International Journal of Behavioral Sciences, 2026)
Healthcare workers (HCWs) in India, particularly in resource-limited settings, face high levels of occupational stress, yet structured stress-reduction interventions remain underutilized. Mindfulness-Based Stress Reduction (MBSR) offers a potential solution, but implementation challenges persist. To assess the effectiveness of an 8-week MBSR programme in reducing stress and enhancing mindfulness among HCWs in South India, and to identify barriers to its successful implementation across urban and rural settings. A quasi-experimental study was conducted with 450 HCWs (doctors, nurses, technicians) from 10 urban and rural hospitals. Participants were randomized into MBSR (n = 225) and control (n= 225) groups. The Perceived Stress Scale (PSS) and the Five Facet Mindfulness Questionnaire (FFMQ) were used for evaluation before and after the intervention. Qualitative data on implementation barriers were also collected. The MBSR group showed a significant reduction in stress scores (28.4 ± 4.2 to 19.1 ± 3.8; p <0.001), while the control group saw minimal changes (27.9 ± 4.5 to 26.3 ± 4.1; p = 0.12). Significant improvements were observed in the FFMQ domains of ‘Observing’ (24.1 ± 3.5 to 28.9 ± 2.7; p < 0.001) and ‘Non-Reactivity to Inner Experience’ (18.3 ± 2.8 to 22.4 ± 3.1; p = 0.001). Barriers to implementation included limited respite time (82% rural vs. 65% urban), cultural stigma (53% rural vs. 28% urban), and inadequate institutional support (18% rural vs.40% urban). The MBSR programme was effective in reducing stress and enhancing mindfulness among HCWs in South India. However, successful implementation demands region-specific planning to overcome challenges such as time constraints, stigma, and inconsistent institutional backing,especially in rural settings.
Keywords: Mindfulness Stress Management (MBSR); Rural-Urban Barriers; South India; healthcare workers; occupational health; perceived stress